Country profile: sport policy in Uganda - Emmanuel Sebata; Yanli Li (Informa UK Limited, 2022)
Explicitly tracing the current sport system structure, status and policy framework, this article is set out to review and provide a broad understanding of Uganda’s sports policies. It examines historical overview, government involvement, administrative setup and the wider sport policy setting including the funding mechanisms, elite sport participation and performance, legal framework, key trends, and emerging sport policy issues. The article offers an up-to-date overview of Uganda’s sport policy landscape largely since it gained its independence from the colonial rulers in 1962. However much Uganda is regarded as one of the African sports powerhouses, relatively little research has been published on both its earlier and contemporary sport policies, and even less on the implementation, administration, management and performance of elite sport. It argues that the main ambitions and priorities of the Ugandan government should not only be concentrated on attaining mass sports participation, elite sport success, national identity, economic transformation and a healthy and active population but rather on striking a balance between them. The article delineates the starting point for improving sports development through reshaping Uganda’s sport policy.